Essential forensic pathology : core studies and exercises - Corrigan, Gilbert Edward (Boca Raton : CRC Press, 2012)
'A thorough and unique reference, this text is ideal for those entering the field of forensic pathology. Beginning with a brief review of the essentials, the book outlines 15 different sets of learning experiences available to a trainee. Providing comprehensive coverage of causes and modes of death, the book focuses on 40 autopsy experiences through which the forensic pathology resident is likely to rotate. For each topic, the chapters provide an emphasis on the objective to be reached and include discussion questions as a guide'--Provided by publisher.
In Process PDAL
Includes bibliographical references and index.
Keywords: Forensic pathology; Forensic Pathology -- education -- Problems and Exercises; Forensic pathology